Pengaruh Magang Wirausaha Merdeka, Motivasi, Penggunaan Media Sosial Dan Self-Efficacy Dalam Meningkatkan Minat Berwirausaha Mahasiswa - Aenuriya Syifana; Mahameru Rosy Rochmatullah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the significance of the influence of independent entrepreneurial internships, motivation, social media usage, and self-efficacy on students' entrepreneurial interest. The method used in this research is correlational with a quantitative approach. The data collection technique used in this study is a questionnaire. The population in this study consists of students who have participated in the Independent Entrepreneurial Program in 2023, totaling 400 students from 8 universities. The sample in this study was taken from 30% of the total population, which is 120 students. The data analysis technique used in this study consists of instrument validity and reliability tests, classic assumption tests (normality test, heteroskedasticity test, and multicollinearity test), multiple regression analysis (t-test and F-test), and determination coefficient. The results of the study concluded that: Hypothesis 1 states that independent entrepreneurial internships have a significant effect on students' entrepreneurial interest. Hypothesis 2 states that motivation has a significant effect on students' entrepreneurial interest. Hypothesis 3 states that social media usage does not have a significant effect on students' entrepreneurial interest. Hypothesis 4 states that self-efficacy has a significant effect on students' entrepreneurial interest. Independent entrepreneurial internships, motivation, social media usage, and self-efficacy collectively or together influence entrepreneurial interest.